Importance of Aahar-Vihar in Anorectal disorders (Gudarogas) According to Ayurveda - Yadav, Munni; Gupta, Rajesh Kumar (International Research Journal of Ayurveda & Yoga, 2021)
One who is established in self, who has balanced Doshas, balanced Agni,(digestive fire) properly formed dhatus, proper elimination of malas, well-functioning bodily processes and whole mind, soul and senses are happy is called a healthy person. The nutritional intake is one amongst the various factors that govern the persons health. The source of all these nutrients is diet. A balanced diet together with balanced sleep and regular physical activity is essential for healthy body. In modern century the lifestyle of human beings is most common reason for disease. Sedentary life style and westernization has led to change in the dietic patterns. Rather than following our traditional dietic regimen which was full of nutrients and fiber the new generation has took to a westernized diet which is deficient in nutrients and fibers. This fiber deficient diet is one of the chief causes behind the Anorectal disorders. Also, such diet vitiates our Agni (digestive fire) & leads to such disorders. Primary principal treatment of these anorectal disorders in Ayurveda to correct our Agni (digestive fire) along with detoxification our body.